LMS-Based Variable Step-Size Algorithms: A Unified Analysis Approach - Saeed, Muhammad Omer Bin (Arabian journal for science and engineering (2011), 2017)
Several variable step-size strategies have been suggested in the literature to improve the performance of the least-mean-square (LMS) algorithm. Although they enhance performance, a major drawback is the complexity in the theoretical analysis of these algorithms. Researchers use several assumptions to find closed-form analytical solutions. This work presents a unified approach for the analysis of variable step-size LMS algorithms. The approach is then applied to several variable step-size strategies, and theoretical and simulation results are compared.